2019
DOI: 10.1017/s0033291719002885
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala functional connectivity in major depression – disentangling markers of pathology, risk and resilience

Abstract: BackgroundLimbic-cortical imbalance is an established model for the neurobiology of major depressive disorder (MDD), but imaging genetics studies have been contradicting regarding potential risk and resilience mechanisms. Here, we re-assessed previously reported limbic-cortical alterations between MDD relatives and controls in combination with a newly acquired sample of MDD patients and controls, to disentangle pathology, risk, and resilience.MethodsWe analyzed functional magnetic resonance imaging data and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 47 publications
4
39
1
1
Order By: Relevance
“…However, first-degree relatives also show increased functional connectivity between the perigenual ACC and the amygdala compared with healthy controls and people with MDD, suggesting that this might be a mechanism for resilience. 49 As well, in a sample of 12 women, increased effective connectivity has been reported between the left-sided subgenual ACC and the amygdala while implicitly processing dynamic fearful faces. 50 Thus, both increased and decreased functional connectivity between the rostral ACC and the amygdala have been described.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, first-degree relatives also show increased functional connectivity between the perigenual ACC and the amygdala compared with healthy controls and people with MDD, suggesting that this might be a mechanism for resilience. 49 As well, in a sample of 12 women, increased effective connectivity has been reported between the left-sided subgenual ACC and the amygdala while implicitly processing dynamic fearful faces. 50 Thus, both increased and decreased functional connectivity between the rostral ACC and the amygdala have been described.…”
Section: Discussionmentioning
confidence: 91%
“…48 Functional connectivity between the amygdala and the perigenual ACC was negatively associated with negative affect in controls. 49 Carriers of the 5-HTTP short allele have reduced functional connectivity between the subgenual region and the amygdala during the perception of threatening faces, compared with carriers of the long allele. 8 Reduced perigenual-amygdalar functional connectivity has been tested as an intermediate phenotype for at-risk individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study that focused on large‐scale intrinsic brain networks reported that MDD patients tended to exhibit reduced connectivity within GM, especially in the networks associated with diverse cognitive, emotional, and self‐reflective functions 20 . Additional MDD studies have reported that resting‐state connections were decreased between a variety of GM regions, but mainly including the amygdala 21 and dorsolateral prefrontal and posterior cingulate corices 22 . Given these findings, it is possible that global GM‐connection impairments may be a potential pathological feature of MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Die kortikolimbische Regulation kehrt nicht nur psychopatho logische Zustände um, sondern zeigt sich auch bei gesunden Per sonen als neuronales Korrelat der Emotionsregulation [54]. Wei ter gibt es inzwischen eine Reihe neurokognitiver Resilienzstudien, die auf eine ausgeglichene kortikolimbische Regulation als Resi lienzmechanismus hinweisen [34,[55][56][57][58][59][60]. Diese Studien sind vor allem querschnittlich und kategorial, d. h. es wurden Gruppen un tersucht, die Stressoren erlebt hatten und dann diejenigen mit und ohne Traumafolgestörung verglichen.…”
Section: Stressregulation (Regulation Negativen Affektes)unclassified